Lou Gehrig : The Lost Memoir - Gaff, Alan D., 1903-1941 (New York : Simon & Schuster, 2020)
"The lost memoir from baseball icon Lou Gehrig-a major historical discovery, published for the first time as a book, with "color commentary" from historian Alan Gaff. In 1927, the legendary Lou Gehrig sat down to write the remarkable story of his life and career. He was at his peak, fresh off a record-breaking season with the fabled 27 World Series champion Yankees. It was an era unlike any other. Gehrigs personal remembrances were published that year as popular weekly columns in The Oakland Tribune. Until now, those pages were lost to history. Lou comes alive in his captivating memoir. It is a heartfelt rags-to-riches tale about a poor kid from New York who grew up to become one of the greatest. He takes us to his childhood home, to Columbia University where he flashed as a prospect, all the way to the dugout at Yankee Stadium where he recounts his first major league hit and bonding with Babe Ruth. There is a real poignancy to this tale. Built like a heavyweight boxer, "Iron Horse" Lou was one of the most powerful men to play the game. Off the field he was a shy, gentle soul. He would die prematurely from ALS, a degenerative neuromuscular disorder now known as Lou Gehrigs Disease. Here is Lou back at bat-Hall of Famer, All Star, and MVP. Lou Gehrig is a monument and tribute to a singular life and career"--
"Portions of this text were previously published in 1927 by The Oakland Tribune as Following the Babe."
Keywords: Gehrig, Lou, -- 1903-1941.; Baseball players -- United States; Biography; Baseball -- United States; History -- 20th century; Biography